ENVIROMENTAL, SOCIAL, AND GOVERNANCE (ESG), FINANCIAL REPORTING QUALITY, AUDIT QUALITY ON INVESTMENT EFFICIENCY AND FIRM VALUE - Wahyu Ningsih; Eny Maryanti (Antis Publisher, 2025)
Objective: This study aims to analyze the influence of Environmental, Social, and Governance (ESG), financial reporting quality, and audit quality on investment efficiency and firm value among publicly listed companies in Indonesia. Method: Using a quantitative research design, the study examines 86 non-financial and non-insurance firms listed on the Indonesia Stock Exchange over the 2017–2023 period, selected through purposive sampling. Multiple linear regression analysis was conducted using SPSS to evaluate the relationships among the variables. Results: The findings indicate that ESG does not significantly affect investment efficiency, whereas both financial reporting quality and audit quality have significant positive effects on investment efficiency. Additionally, ESG and financial reporting quality are shown to have no significant effect on firm value, while audit quality significantly enhances firm value. Novelty: This study contributes to the literature by simultaneously evaluating financial and non-financial determinants of investment efficiency and firm value within an emerging market context, providing empirical evidence that audit quality plays a more influential role than ESG performance or reporting quality in shaping firm value in Indonesia.